2016
DOI: 10.1016/j.thromres.2015.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma anti-FXa level as a surrogate marker of the adequacy of thromboprophylaxis in critically ill patients: A systematic review

Abstract: Based on the current literature, no definite conclusions can be drawn on targeted anti-FXa level in critically ill patients when using LMWH thromboprophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 41 publications
1
26
0
1
Order By: Relevance
“…We found that continuous intravenous enoxaparin infusion as thromboprophylaxis therapy resulted in lower plasma anti-FXa concentration than standard subcutaneous administration during the first 24 h. No associations between anti-FXa concentration and clinical endpoints (bleeding or thromboembolic complications) were detected. This result supports our previous findings [4].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that continuous intravenous enoxaparin infusion as thromboprophylaxis therapy resulted in lower plasma anti-FXa concentration than standard subcutaneous administration during the first 24 h. No associations between anti-FXa concentration and clinical endpoints (bleeding or thromboembolic complications) were detected. This result supports our previous findings [4].…”
Section: Discussionsupporting
confidence: 94%
“…The monitoring of anticoagulant effect is not generally recommended when using LMWHs [3]. Nonetheless, the measurement of plasma anti-factor Xa (anti-FXa) concentration has been described, although its efficacy as a means of monitoring therapeutic effect and association with clinical thromboembolic events is thought to be inadequate [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, previous trials have shown inadequate Anti-Xa response in critically unwell patients, including those with acute burns (10,11). The clinical implication of this subtherapeutic response in terms of VTE diagnoses is unclear (12).…”
Section: Introductionmentioning
confidence: 98%
“…20 In critically ill patients, the incidence of VTE varies form 5 to 16% despite standardized pharmacologic prophylaxis. 27 Therefore, anticoagulant monitoring could be indicated in these patients. VCAs could help find the correct dose in cases where aPTT and anti-Xa testing are not conclusive.…”
Section: Viscoelastic Coagulation Assays In Different Patient Populatmentioning
confidence: 99%